Effectiveness of adjuvant chemotherapy for elderly patients with lymph node-positive colorectal cancer - Tominaga, Tetsuro (World J Surg Oncol, 2016)
BACKGROUND: Several guidelines state that postoperative adjuvant chemotherapy (AC) confers survival benefits to patients with lymph node-positive colorectal cancer. However, older patients are usually not administered AC due to the higher risk of side effects. The aim of this study was to evaluate the benefit of AC for elderly patients (EP) and examine its tolerability. METHODS: Data from 204 patients with lymph node-positive colon cancer were retrospectively analyzed. Patients were subdivided into two groups: EP, >75 years old (n = 53) and young patients (YP), <75 years old (n = 151). Clinicopathological features, type of chemotherapy, and outcomes were compared between groups. RESULTS: Frequency of comorbidities and performance status were significantly higher in EP (p < 0.01 each), a greater proportion of YP (76 %) than EP received AC (40 %, p < 0.01), and YP received combination therapy more frequently than EP (p < 0.01). In terms of side effects, few EP showed severe side effects. Both YP and EP gained survival benefits from AC (p = 0.07 and p < 0.01, respectively). CONCLUSIONS: AC should not be withheld from eligible EP purely because of age. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12957-016-0959-5) contains supplementary material, which is available to authorized users.